Expectativa docente, processos de enturmação e proficiência em matemática: o que a rede municipal de Belo Horizonte nos mostra? - Tatiana Maria da Cruz (2021)
This research is situated in the field of studies on school effect and teacher effect. The former investigates characteristics of schools, such as the context in which they are inserted, as well as their practices, which may produce differences in students’ trajectories. The latter searches for evidence of more efficient teaching practices in order to improve student performance. The school effect is associated with the class effect, which refers to forms of class organization and composition. Studies have shown that the criteria adopted in the process of class organization (known in Portuguese as “enturmação”) influence academic outcomes. This research aimed to investigate class composition criteria in schools; to analyze teacher’s expectations regarding students’ educational potentiality, given the composition and performance of a class; and to analyze teachers’ perceptions regarding the class composition. To achieve such objectives, the investigation was held in two stages: the first one encompassed the exploration of quantitative data; and the second one encompassed the analysis of qualitative data. In the first stage, we used data derived from Prova Brazil 2017 – a large scale national-level assessment instrument consisting of reading and mathematical proficiency tests and contextual questionnaires. We analyzed the tests taken by students in the 5th and 9th grade of elementary school, and questionnaires answered by the teacher and the director of the municipal education system in Belo Horizonte. In the second stage, we selected a school in order to conduct interviews. This selection was made through a statistical test set to assess which schools had displayed significant differences in mathematical proficiency among classes in the 2013, 2015 and 2017 editions of Prova Brazil. Six professionals from different positions in the selected school were interviewed. The results of the first stage demonstrated that the criterion for class organization most adopted by the directors of the municipal education system in Belo Horizonte is age homogeneity, followed by school performance heterogeneity. Expectations are lower when the class has a greater number of black students, students who have failed Mathematics classes before, or students who have had lower averages in Mathematics. The interviews achieved results that are not measured by Prova Brazil’s questionnaires on the organization of classes. The most adopted criterion in the target school is “behavioral heterogeneity”; i.e., the school is partial to arranging classes with more and less disciplined students, in order not to allow many undisciplined students to share the same class. Color/race, school trajectory and performance did not appear as organizational criteria for class composition in the interviews; however, an unexpected theme emerged: school professionals displayed the understanding that the subject of Mathematics is more difficult for girls. We concluded that there are quite subtle mechanisms that may contribute to producing differences in students’ learning. A limitation of this research was the impossibility of conducting field work, for it was not allowed due to the Covid-19 pandemic. This kind of work would have been relevant, as it would have allowed for observations within classrooms, school staff meetings and other events and spaces in the school environment, providing us with more data for understanding the issues studied in this research.